(untitled) (Global Journal of Medical Research, 2021)
Chronic kidney disease (CKD)#x2014;or chronic renal failure (CRF), as it was historically termed#x2014;is a term that encompasses all degrees of decreased kidney function, from damaged#x2013; at risk through mild, moderate, and severe chronic kidney failure. Epidemics of CKD of uncertain etiology (CKDu) are emerging around the world. Highlighting common risk factors for CKD of uncertain etiology across various regions and populations may be important for health policy and public health responses. Prevalence of CKD of unknown (CKDu) etiology is being increasingly considered as an emerging etiology, especially in the developing countries, with environmental predisposition to hot humid climate, dehydration and toxic metal contaminations.